2017
DOI: 10.5897/ajar2017.12679
|View full text |Cite
|
Sign up to set email alerts
|

Slaughter performance and meat quality of intact and castrated Washera sheep kept under feedlot condition

Abstract: A study was conducted to evaluate the feedlot performance in carcass traits and meat quality of intact and castrated Washera sheep under low (300 g/day) and high (450 g/day) dry matter (DM) levels of concentrate mix supplementation. The concentrate mix contained 68% wheat bran and 32% noug seed cake. 24 sheep (12 intact and 12 castrated) with age range of 9 to 10 months and initial weight of 24.1±1.8 kg (mean ± SD) were used. A randomized complete block design in a 2x2 factorial treatment arrangement (2 sex ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
3
5
1
Order By: Relevance
“…e fiber content of Teff straw was comparable with that in [32] (77.65%) and [33] (77.5%). Similarly, the NDF value of hay (73.72%) was comparable with the reports in [34] with 72.20%, but lower than that in [35] with 79.40%. e proportion of fiber content in hay is greatly influenced by the stage of maturity at cutting and postharvest management [12].…”
Section: Fiber Fraction and Digestibilitysupporting
confidence: 83%
“…e fiber content of Teff straw was comparable with that in [32] (77.65%) and [33] (77.5%). Similarly, the NDF value of hay (73.72%) was comparable with the reports in [34] with 72.20%, but lower than that in [35] with 79.40%. e proportion of fiber content in hay is greatly influenced by the stage of maturity at cutting and postharvest management [12].…”
Section: Fiber Fraction and Digestibilitysupporting
confidence: 83%
“…Costa also found a significant (p>0.05) effect of hot carcass and dressing percentage which was very much similar with this study [38]. Melese et al [41] stated that the sheep consuming higher level of concentrate supplements had significant heavier carcass than lower level of concentrate feed. These results supported the present study.…”
Section: Effect Of Concentrate Feeds On the Carcass Traitssupporting
confidence: 88%
“…Their results support the findings of the present study as all supplemented lambs were higher than the control on these parameters. Melese et al (2017) also confirmed the same trend of carcass traits improvement on Washera sheep due to supplementation of hay by concentrates. According to Lloyd et al (1981) and Žgur et al (2003), higher values of carcass traits are apparent for heavier lambs.…”
Section: Carcass Characteristics and Yieldsupporting
confidence: 76%
“…Color and pH taken at 1 and 24 h post mortem of Longismus dorsi meat of Washera and Afar sheep were not influenced by level of supplementation and types of feed (Melese et al, 2017;Ahmed et al, 2012). Likewise, Sheridan et al (2003) reported no effect of diet on color of 8-9-10-rib cut meat of mutton Merino lambs.…”
Section: Physicochemical Characteristics and Chemical Composition Of mentioning
confidence: 96%